Introduction to the Computer Simulations: Script - Novak, Nejc; Borovinšek, Matej; Vesenjak, Matej; Ren, Zoran (University of Maribor Press, 2024)
The script entitled „Introduction to the computer simulations“ in the field of Engineering Computer Simulations is intended as a study aid in the lectures of the courses Engineering Computer Simulations for foreign students at the University of Maribor and for students at Kumamoto University, Japan. It explains all the material that students must master in these subjects, and is consistent with the subject curriculum. The basics of computational simulations, based on the Finite Element Method, are given from the theoretical basics to step-by-step preparation of simple computational models and their analysis in PrePoMax software.